Portal hypertension due to Echinococcus alveolaris: a case report. - Poyrazoglu, Orhan Kursat; Ataseven, Huseyin; Bektas, Sevim; Aydin, Ayse; Yalniz, Mehmet; Celebi, Selman; Bahcecioglu, Ibrahim Halil (My University, 2007)
Infection of the liver with Echinococcus alveolaris (EA) contemplates with a fatal course though it is a rare condition. We present herein a patient with upper gastrointestinal bleeding due to portal hypertension caused by the involvement of the liver with EA.
Keywords: Echinococcosis, Hepatic; Gastrointestinal Hemorrhage; Humans; Hypertension, Portal; Male; Middle Aged; article; case report; gastrointestinal hemorrhage; human; liver hydatid cyst; male; middle aged; parasitology; portal hypertension